Feature‐Driven Generalization of Isobaths on Nautical Charts: A Multi‐Agent System Approach. Issue 1 (18th June 2015) - Guilbert, Eric
Abstract : A nautical chart provides a schematic view of the seafloor where isobaths (contour lines joining points of same depth) and depth soundings are generalized to highlight undersea features that form navigational hazards and routes. Considering that the process is ultimately driven by features and their significance to navigation, this article proposes a generalization strategy where isobath generalization is controlled by undersea features directly. The seafloor is not perceived as a continuous depth field but as a set of discrete features composed by groups of isobaths. In this article, generalization constraints and operators are defined at feature level and composed of constraints and operators applying to isobaths. In order to automate the process, a multi‐agent system is designed where features are autonomous agents evaluating their environment in order to trigger operations. Interactions between agents are described and an example on a bathymetric database excerpt illustrates the feasibility of the approach.